Thermodynamic Perfomance Comparison of Working Fluids Based on Organic Rankine Cycle in Waste Power Plants - Kopong Ola Kornelis; Waluyo Joko; Cahyadi; Agustina Lina (E3S Web of Conferences)
The use of alternative fuels, other than fossil fuels, is an interesting issue for power generation today. The power plant option used is a waste power plant that utilizes the heat exhausted from the garbage. The study investigate a thermodynamic analysis four working fluids at a power plant based on the organic Rankine cycle (ORC) using waste heat that comes out of an incinerator located in Soreang Bandung. The working fluids are R123, n-butane, n-pentane, and R245fa. The temperature of the heat vapor coming out of the incinerator is 450 °C with a heat vapor flow of 3 kg/s. Consideration Thermodynamic analysis was performed with a turbine inlet temperature of 130 °C because one of the fluids was already close to the critical temperature. (EES). Based on the thermodynamic analysis of each fluid, R123 produced the most power (91.22 kW), whereas R254fa provided the lowest power (87.92 kW). The plant exhibited the maximum power consumption at 25.93 kW and the lowest at 19.51 kW. The n-pentane fluid demonstrated the highest thermal efficiency at 8.86%, while the n-butane fluid had the lowest thermal efficiency at 7.94%.